ANALISIS PENGARUH KETERBUKAAN EKONOMI TERHADAP STABILITAS NILAI TUKAR PADA NEGARA-NEGARA ISLAM - B61112039, IIN KURNIAWAN (Jurnal Ekonomi Daerah (JEDA), 2016)
The openness economy of a country is always being associated with import export activity undertaken by these countries. Therefore, many of the assumptions stated that the openness of the economy can affect the exchange rate of a country, on the base of the activity of international trade of the country. This research aims to look at the influence of economic openness towards the stability of the exchange rate in the Islamic State. This research is using quantitative data. The data used here in the form of report were taken from the World Bank to look at the country's exchange rate against the U.S. Dollar and openeness economy. This research takes the subject, namely Indonesia, Malaysia and Brunei Darussalam, by looking at their exchange rate movements from 1984-2013. The results showed that the results of the estimation by using testing partially stated that economic openness degree highly statistically significant $/US exchange rate influence on Î± = 5% in the country of Malaysia and Brunei, while for Indonesia cannot be determined simply by the openness of its economy. Keywords ; Economic Openness, Stability, Exchange Rate, Islamic Country